A multi-component copolymer dispersant for grinding heavy calcium carbonate and preparation method thereof
The multivariate copolymerization dispersant prepared by copolymerizing acrylic acid, parastyrene sulfonic acid, maleic acid and hydroxyethyl acrylate has solved the problem of large amount of calcium carbonate dispersant used and high cost in the prior art, and achieved the effect of reducing the viscosity of heavy calcium carbonate slurry and improving stability.
Patent Information
- Application Number
- CN202411663383.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-20
- Publication Date
- 2025-04-04
AI Technical Summary
The existing calcium carbonate dispersant is large in use, high in cost and has a negative impact on the environment, making it difficult to effectively reduce the viscosity of heavy calcium carbonate slurry.
A multi-copolymerization dispersant composed of acrylic acid, para-styrenesulfonic acid, maleic acid and hydroxyethyl acrylate is prepared by free radical copolymerization reaction to adjust the pH value of the product to improve the dispersion effect.
The viscosity of heavy calcium carbonate slurry is significantly reduced, the performance and stability of the abrasive slurry is improved, the use of dispersant is reduced, and the production cost is reduced.
Smart Images

Figure BDA0005144014370000071
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of dispersants for calcium carbonate, and in particular to a multi-component copolymer dispersant for grinding heavy calcium carbonate and a preparation method thereof. Background Art
[0002] Dispersants are important additives in the grinding of pigments or fillers such as calcium carbonate and the dispersion of coatings. They can improve grinding efficiency, increase particle size, improve viscosity, improve the stability of slurries and coatings, and improve various properties such as paper smoothness, whiteness, ink absorption, surface strength, coating gloss, and printing gloss. Polymer sodium salts of vinyl acid are widely used in this field, among which low molecular weight sodium polyacrylate aqueous solution is the main product in this field. However, the main raw material of dispersants is currently petroleum-based raw materials, which are non-renewable. Therefore, the cost of raw materials is increasing day by day, and the large amount of use has many negative effects on the environment, and the operating pressure of enterprises is also increasing day by day. Single-component polymers have simple structures and fewer functional groups, and it is difficult to improve performance. Therefore, it is urgent to develop dispersant products with less use and better effects.
[0003] CN101391194A discloses a ternary copolymer dispersant, which is formed by free radical copolymerization of acrylic acid, sodium styrene sulfonate, hydroxypropyl acrylate or hydroxyethyl methacrylate. The ternary copolymer has high thermal stability, good water solubility, good adaptability to acids and alkalis, and good dispersion stability, and has a good dispersing effect on calcium carbonate, zinc oxide, barium sulfate, titanium dioxide, etc.
[0004] CN101391193A discloses an acrylic polymer dispersant, which is formed by free radical copolymerization of acrylic acid, sodium styrene sulfonate and maleic anhydride. The copolymer has high thermal stability, good water solubility, good adaptability to acids and alkalis and good dispersion stability, and has a good dispersing effect on inorganic particles such as calcium carbonate, zinc oxide, barium sulfate and titanium dioxide.
[0005] Multi-component copolymer dispersants have excellent dispersing properties and stability, and further research on more types of multi-component copolymer dispersants has great research value. Summary of the invention
[0006] The technical problem to be solved by the present invention is to provide a multi-component copolymer dispersant for grinding heavy calcium carbonate and a preparation method thereof, so as to reduce the viscosity of calcium carbonate slurry.
[0007] The present invention is achieved by adopting the following technical solutions:
[0008] A multi-component copolymer dispersant for grinding heavy calcium carbonate is prepared by copolymerization of acrylic acid, p-styrene sulfonic acid, maleic acid and hydroxyethyl acrylate. The weight percentages of the copolymer monomers are respectively: 20-60% of acrylic acid, 20-60% of p-styrene sulfonic acid, 10-30% of maleic acid and 10-30% of hydroxyethyl acrylate, and the sum of the weight percentages of the components is 100%. The sum of the weight percentages of acrylic acid and p-styrene sulfonic acid is 60-80%, and the sum of the weight percentages of maleic acid and hydroxyethyl acrylate is 20-40%.
[0009] Preferably, the weight percentages of the comonomers are: 20-50% acrylic acid, 20-50% p-styrenesulfonic acid, 10-20% maleic acid, and 10-20% hydroxyethyl acrylate, and the sum of the weight percentages of the components is 100%; and the sum of the weight percentages of acrylic acid and p-styrenesulfonic acid is 70-80%, and the sum of the weight percentages of maleic acid and hydroxyethyl acrylate is 20-30%.
[0010] The preparation method of the above-mentioned multi-copolymer dispersant for grinding heavy calcium carbonate comprises the following steps: adding at least one comonomer into a reactor, adding an appropriate amount of water to mix to form a kettle bottom material, heating to a polymerization reaction temperature, and simultaneously dripping an initiator, a reducing agent and the remaining comonomers to carry out a free radical copolymerization reaction. After the reaction is completed, adjusting the pH value of the reaction product to 5-9 with an alkaline neutralizer to obtain the multi-copolymer dispersant for grinding heavy calcium carbonate.
[0011] Preferably, the weight proportions of the components are as follows: 30-65 parts of the comonomer, 0.3-2 parts of the initiator, 1-5 parts of the reducing agent, and 50-105 parts of the neutralizing agent.
[0012] The bottom material may contain one comonomer, such as maleic acid or hydroxyethyl acrylate, or two comonomers, such as maleic acid and hydroxyethyl acrylate, or acrylic acid and p-styrene sulfonic acid, or three comonomers, such as maleic acid, acrylic acid and p-styrene sulfonic acid, or hydroxyethyl acrylate, acrylic acid and p-styrene sulfonic acid, or four comonomers may be added at the same time as the bottom material. One comonomer in the bottom material may be the entire amount of the comonomer, but the amount of the comonomer added in the bottom material does not exceed 80% of the total weight of the comonomers, preferably does not exceed 65%, and most preferably does not exceed 50%.
[0013] The inventor has found that, compared with the existing ternary copolymer dispersant, the copolymer formed by copolymerization of acrylic acid, p-styrene sulfonic acid, maleic acid, and hydroxyethyl acrylate is used as a dispersant and applied to heavy calcium carbonate grinding, which can obtain unexpectedly lower slurry viscosity, improve the performance and stability of the grinding slurry, effectively reduce the amount of dispersant used, and reduce production costs while improving product performance. Its specific principle is not very clear. The inventor speculates that it may be because maleic acid has more carboxyl groups than acrylic acid, thereby greatly improving the synergistic effect of functional groups such as carboxyl groups, sulfonic acid groups, and hydroxyl groups in the copolymer, greatly enhancing the adsorption capacity of the copolymer and calcium carbonate particles, further reducing the interfacial tension between solid and liquid, making the surface of the condensed solid particles easier to wet, and the polar end of the dispersant has a stronger affinity with water, further increasing the degree of water wetting of the solid particles, so that the solid particles are separated from each other due to electrostatic repulsion, and further enhancing the dispersion effect. Based on the above findings, the inventor has completed the present invention.
[0014] The initiator is selected from at least one of sodium persulfate, potassium persulfate, ammonium persulfate, hydrogen peroxide, tert-butyl hydroperoxide, cyclohexanone peroxide, benzoyl peroxide, and azo initiators.
[0015] The reducing agent is selected from at least one of sodium bisulfite, sodium sulfite, sodium pyrosulfite, potassium sulfite, sodium thiosulfate, ferrous pyrophosphate, sodium pyrophosphate, sodium phosphite, sodium hypophosphite, sodium dihydrogen phosphate, and vitamin C.
[0016] Preferably, the initiator and the reducing agent are prepared into a 15-30 wt % aqueous solution.
[0017] The initiator, reducing agent and other comonomers are added dropwise for 2-6 hours. After the addition is completed, the reaction is continued for 0.5-2 hours. The reaction temperature is controlled between 80-100°C.
[0018] The neutralizing agent is selected from at least one of sodium hydroxide, magnesium hydroxide, potassium hydroxide, calcium hydroxide, potassium carbonate, sodium carbonate, ammonia water, and organic amines.
[0019] As a more preferred technical solution, a method for preparing a multi-component copolymer dispersant for grinding heavy calcium carbonate comprises the following steps: adding maleic acid and hydroxyethyl acrylate into a reactor, adding an appropriate amount of water to mix and form a bottom material, heating to a polymerization reaction temperature, and simultaneously dripping an initiator, a reducing agent, acrylic acid and p-styrene sulfonic acid to carry out a free radical copolymerization reaction; after the reaction is completed, adjusting the pH value of the reaction product to 5-9 with an alkaline neutralizer to obtain the multi-component copolymer dispersant for grinding heavy calcium carbonate; wherein the weight percentages of the copolymerized monomers are: 20-50% acrylic acid, 20-50% p-styrene sulfonic acid, 10-20% maleic acid, and 10-20% hydroxyethyl acrylate, and the sum of the weight percentages of the components is 100%; and the sum of the weight percentages of acrylic acid and p-styrene sulfonic acid is 70-80%, and the sum of the weight percentages of maleic acid and hydroxyethyl acrylate is 20-30%.
[0020] Further preferably, the weight proportions of the components are as follows: 100 parts of the comonomer, 0.9-3 parts of the initiator, and 1-4 parts of the reducing agent; the initiator, reducing agent, acrylic acid and p-styrene sulfonic acid are added dropwise for 3-5 hours, and the reaction is continued for 1-2 hours after the addition is completed, and the reaction temperature is controlled between 90-100°C.
[0021] The present invention selects a variety of different monomers for copolymerization, and then obtains a polymer dispersant containing a variety of different types and proportions of functional groups and structures, thereby achieving synergistic effects, improving performance, and reducing costs. The dispersant of the present invention shows more excellent performance, and the dispersion effect is still very good when the usage amount is greatly reduced, and the viscosity and dispersion stability of the heavy calcium slurry are greatly improved. Compared with traditional dispersants, it has obvious advantages and broader application prospects. DETAILED DESCRIPTION
[0022] The following description is used to disclose the present invention so that those skilled in the art can implement the present invention. The preferred embodiments described below are only used as examples, but are not used to limit the scope of the present invention. Those skilled in the art can think of other obvious variations. The basic principles of the present invention defined in the following description can be applied to other embodiments, variations, improvements, equivalent solutions, and other technical solutions that do not deviate from the spirit and scope of the present invention.
[0023] The instruments or raw materials in the present invention that do not indicate the manufacturer are all conventional commercial instruments or raw materials. If the detection indicators involved in the embodiments of the present invention are not mentioned, they are all detected by conventional detection methods in the art.
[0024] Example 1
[0025] Take 1.8g of sodium persulfate to prepare a 15% initiator aqueous solution, 6g of sodium hypophosphite to prepare a 20% reducing agent aqueous solution, weigh 50g of acrylic acid and 100g of p-styrene sulfonic acid and mix them evenly to make a mixed monomer for use. Add 90g of water, 30g of maleic acid, and 20g of hydroxyethyl acrylate to a 1-liter four-necked flask and stir evenly. Heat the bottom of the kettle to 100°C, and start dripping the initiator, reducing agent and mixed monomer under stirring. Control the dripping time to 3h, and try to keep the dripping at the same time. After the dripping is completed, continue to keep the reaction warm for 1h. Cool to room temperature and neutralize with sodium hydroxide and ammonia water in a molar ratio of 3:1, and adjust the pH value to 7.05. The solid content is adjusted to 30wt%, and the material is discharged after stirring evenly to obtain the product.
[0026] Example 2
[0027] Take 2g of ammonium persulfate to prepare a 20% aqueous initiator solution, 8g of sodium sulfite to prepare a 25% reducing agent solution, weigh 80g of acrylic acid and 70g of p-styrene sulfonic acid and mix them evenly to prepare a mixed monomer for use. Add 90g of water, 25g of maleic acid, and 25g of hydroxyethyl acrylate to a 1-liter four-necked flask and stir evenly. Heat the bottom of the kettle to 95°C, and start dripping the initiator, reducing agent and mixed monomer under stirring. Control the dripping time to 4h, and try to keep the dripping complete at the same time. After the dripping is completed, continue to keep the reaction warm for 1.5h. Cool to room temperature and neutralize with sodium hydroxide to adjust the pH value to 6.95. The solid content is adjusted to 30wt%, and the material is discharged after stirring evenly to obtain the product.
[0028] Example 3
[0029] Take 8g of hydrogen peroxide to prepare a 15% initiator aqueous solution, 20g of vitamin C to prepare a 15% reducing agent aqueous solution, weigh 100g of acrylic acid and 40g of p-styrene sulfonic acid and mix them evenly to make a mixed monomer for use. Add 100g of water, 40g of maleic acid, and 20g of hydroxyethyl acrylate to a 1-liter four-necked flask and stir evenly. Heat the bottom of the kettle to 90°C, and start dripping the initiator, reducing agent and mixed monomer under stirring. Control the dripping time to 5h, and try to keep the dripping complete at the same time. After the dripping is completed, continue to keep the reaction warm for 2h. Cool to room temperature and neutralize with sodium hydroxide, and adjust the pH value to 7.03. The solid content is adjusted to 30wt%, and the material is discharged after stirring evenly to obtain the product.
[0030] Comparative Example 1
[0031] Compared with Example 1, maleic acid is not added to the comonomer, and its amount is replaced by hydroxyethyl acrylate. The other steps are the same as those in Example 1. The specific reaction process is as follows:
[0032] Take 1.8g of sodium persulfate to prepare a 15% initiator aqueous solution, 6g of sodium hypophosphite to prepare a 20% reducing agent aqueous solution, weigh 50g of acrylic acid and 100g of styrene sulfonic acid and mix them evenly to make a mixed monomer for use. Add 90g of water and 50g of hydroxyethyl acrylate to a 1-liter four-necked flask and stir evenly. Heat the bottom of the kettle to 100°C, and start dripping the initiator, reducing agent and mixed monomer under stirring. Control the dripping time to 3h, and try to keep the dripping at the same time. After the dripping is completed, continue to keep the reaction warm for 1h. Cool to room temperature and neutralize with sodium hydroxide and ammonia water in a molar ratio of 3:1, and adjust the pH value to 7.05. The solid content is adjusted to 30wt%, and the material is discharged after stirring evenly to obtain the product.
[0033] Comparative Example 2
[0034] Compared with Example 1, hydroxyethyl acrylate is not added to the comonomer, and its amount is replaced by maleic acid. The other steps are the same as those of Example 1. The specific reaction process is as follows:
[0035] Take 1.8g of sodium persulfate to prepare a 15% initiator aqueous solution, 6g of sodium hypophosphite to prepare a 20% reducing agent aqueous solution, weigh 50g of acrylic acid and 100g of p-styrene sulfonic acid and mix them evenly to make a mixed monomer for use. Add 90g of water and 50g of maleic acid to a 1-liter four-necked flask and stir evenly. Heat the bottom of the kettle to 100°C, and start dripping the initiator, reducing agent and mixed monomer under stirring. Control the dripping time to 3h, and try to keep the dripping at the same time. After the dripping is completed, continue to keep the reaction warm for 1h. Cool to room temperature and neutralize with sodium hydroxide and ammonia water in a molar ratio of 3:1, and adjust the pH value to 7.05. The solid content is adjusted to 30wt%, and the material is discharged after stirring evenly to obtain the product.
[0036] Comparative Example 3
[0037] The sample of Comparative Example 1 and the sample of Comparative Example 2 were mixed and compounded in a ratio of 40 wt % of the sample of Comparative Example 1 and 60 wt % of the sample of Comparative Example 2.
[0038] Comparative Example 4
[0039] Compared with Example 1, a single monomer acrylic acid is used, and the amount of other monomers is replaced by acrylic acid. The other steps are the same as in Example 1. The specific reaction process is as follows:
[0040] Take 1.8g of sodium persulfate to prepare a 15% initiator aqueous solution, 6g of sodium hypophosphite to prepare a 20% reducing agent aqueous solution, add 90g of water to a 1-liter four-necked flask, heat the bottom of the kettle to 100°C, and start dripping the initiator, reducing agent and 200g of acrylic acid monomer under stirring. Control the dripping time to 3h, and try to keep the dripping complete at the same time. After the dripping is completed, continue to keep the reaction warm for 1h. Cool to room temperature and neutralize with sodium hydroxide and ammonia water in a molar ratio of 3:1, and adjust the pH value to 7.05. The solid content is adjusted to 30wt%, and the material is discharged after stirring evenly to obtain the product.
[0041] Application Examples
[0042] Take the dispersants of each embodiment and comparative example and conduct the experiment according to the following steps: add 25kg water and 2kg dispersant (same dry weight) into a 150L grinding tank and stir evenly. Add 75kg heavy calcium carbonate powder and grind for 1h before discharging. The particle size analyzer test shows that the weight content of calcium carbonate particles less than 2um is more than 65%. Adjust the solid content to 75%, test the kinematic viscosity, viscosity after 1h and static viscosity after 24h (test three times in parallel and take the average value). The results are shown in Table 2:
[0043] Table 2 Product application performance indicators
[0044]
[0045] Note: The viscosity is at 25℃.
[0046] The above results show that under the same process conditions, the kinematic viscosity of the heavy calcium carbonate slurry prepared by grinding the dispersant prepared by the ternary copolymerization of acrylic acid, p-styrene sulfonic acid and hydroxyethyl acrylate (Comparative Example 1) is 24.3%, 37.5% and 27.6% lower than that of the dispersant prepared by the ternary copolymerization of acrylic acid, p-styrene sulfonic acid and maleic acid (Comparative Example 2). The kinematic viscosity of the heavy calcium carbonate slurry prepared by grinding the dispersant prepared by the ternary copolymerization of acrylic acid, p-styrene sulfonic acid and maleic acid is 24.3%, 37.5% and 27.6% lower than that of the dispersant prepared by the ternary copolymerization of acrylic acid, p-styrene sulfonic acid and maleic acid. The static viscosity after 1h and 24h decreased by 17.1%, 31.2% and 24.3% respectively, while the kinematic viscosity of the heavy calcium carbonate slurry prepared by grinding the dispersant (Example 1) prepared by the multi-polymerization of acrylic acid, p-styrene sulfonic acid, maleic acid and hydroxyethyl acrylate of the present invention, the viscosity after 1h and the static viscosity after 24h decreased by 39.5%, 45.8% and 51.0% respectively, far exceeding the above two comparative dispersants, and the dispersant after the two are compounded (Comparative Example 3), indicating that the copolymerization of the above four monomers produces a significant synergistic effect. From the perspective of tracking viscosity, the viscosity growth rate of the heavy calcium carbonate slurry product obtained by using the dispersant of the present invention is significantly lower than that of the comparative sample, which shows that the product performance of the present invention is significantly better than that of conventional dispersants. The present invention can effectively reduce the usage of the dispersant and improve the performance and stability of the grinding slurry.
[0047] It should be understood by those skilled in the art that the above embodiments are only examples and do not limit the present invention. The purpose of the present invention has been fully and effectively achieved. The functional and structural principles of the present invention have been demonstrated and explained in the embodiments, and the embodiments of the present invention may be deformed or modified in any way without departing from the principles.
Claims
1. A multi-polymer dispersant for grinding heavy calcium carbonate, characterized in that: The invention is copolymerized by acrylic acid, p-styrene sulfonic acid, maleic acid and hydroxyethyl acrylate, wherein the weight percentages of the copolymerized monomers are respectively: 20-60% of acrylic acid, 20-60% of p-styrene sulfonic acid, 10-30% of maleic acid and 10-30% of hydroxyethyl acrylate, and the sum of the weight percentages of the components is 100%; the sum of the weight percentages of acrylic acid and p-styrene sulfonic acid is 60-80%, and the sum of the weight percentages of maleic acid and hydroxyethyl acrylate is 20-40%.
2. The multi-polymer dispersant for grinding heavy calcium carbonate as claimed in claim 1, characterized in that, The weight percentages of the comonomers are: 20-50% acrylic acid, 20-50% p-styrene sulfonic acid, 10-20% maleic acid, and 10-20% hydroxyethyl acrylate, and the sum of the weight percentages of the components is 100%; the sum of the weight percentages of acrylic acid and p-styrene sulfonic acid is 70-80%, and the sum of the weight percentages of maleic acid and hydroxyethyl acrylate is 20-30%.
3. The method for preparing a multi-polymer dispersant for grinding heavy calcium carbonate as claimed in claim 1 or 2, wherein: The method comprises the following steps: adding at least one comonomer into a reactor, adding an appropriate amount of water to mix and form a bottom material, heating to a polymerization reaction temperature, and simultaneously dripping an initiator, a reducing agent and other comonomers to carry out a free radical copolymerization reaction; after the reaction is completed, adjusting the pH value of the reaction product to 5-9 with an alkaline neutralizer to obtain the multi-component copolymer dispersant for grinding heavy calcium carbonate.
4. The method according to claim 3, characterized in that The weight proportions of the components are as follows: 30-65 parts of comonomer, 0.3-2 parts of initiator, and 1-5 parts of reducing agent.
5. The method according to claim 3, characterized in that The initiator is selected from at least one of sodium persulfate, potassium persulfate, ammonium persulfate, hydrogen peroxide, tert-butyl hydroperoxide, cyclohexanone peroxide, benzoyl peroxide, and azo initiators.
6. The method according to claim 3, characterized in that The reducing agent is selected from at least one of sodium bisulfite, sodium sulfite, sodium pyrosulfite, potassium sulfite, sodium thiosulfate, ferrous pyrophosphate, sodium pyrophosphate, sodium phosphite, sodium hypophosphite, sodium dihydrogen phosphate, and vitamin C.
7. The method according to claim 3, characterized in that The initiator, reducing agent and other comonomers are added dropwise for 2-6 hours. After the addition is completed, the reaction is continued for 0.5-2 hours. The reaction temperature is controlled between 80-100°C.
8. The method according to claim 3, characterized in that The neutralizing agent is selected from at least one of sodium hydroxide, magnesium hydroxide, potassium hydroxide, calcium hydroxide, potassium carbonate, sodium carbonate, ammonia water, and organic amines.
9. A method for preparing a multi-component copolymer dispersant for grinding heavy calcium carbonate, characterized in that: The method comprises the following steps: adding maleic acid and hydroxyethyl acrylate into a reactor, adding an appropriate amount of water to mix and form a bottom material, heating to a polymerization reaction temperature, and simultaneously dripping an initiator, a reducing agent, acrylic acid and p-styrene sulfonic acid to carry out a free radical copolymerization reaction; after the reaction is completed, adjusting the pH value of the reaction product to 5-9 with an alkaline neutralizer to obtain the multi-component copolymerization dispersant for grinding heavy calcium carbonate; wherein the weight percentages of the copolymerized monomers are respectively: 20-50% of acrylic acid, 20-50% of p-styrene sulfonic acid, 10-20% of maleic acid, and 10-20% of hydroxyethyl acrylate, and the sum of the weight percentages of the components is 100%; the sum of the weight percentages of acrylic acid and p-styrene sulfonic acid is 70-80%, and the sum of the weight percentages of maleic acid and hydroxyethyl acrylate is 20-30%.
10. The method according to claim 9, characterized in that The weight proportions of the components are as follows: 100 parts of comonomer, 0.9-3 parts of initiator, 1-4 parts of reducing agent; the initiator, reducing agent, acrylic acid and p-styrene sulfonic acid are added dropwise for 3-5 hours, and the reaction is continued for 1-2 hours after the addition is completed, and the reaction temperature is controlled between 90-100°C.
Citation Information
Patent Citations
Acrylics polymeric dispersant and preparation technique and use thereof
CN101391193A
Terpolymer dispersants and preparation technique and use thereof
CN101391194A
Cited By
Preparation method of polymer additive for producing superfine ground calcium carbonate
CN120904401A